Evaluation of the Results of Food Plant Seed Breeding Training in 2013 on the Development Unit of Food Plant Seeds and Horticulture, West Kalimantan Province - Gunawan Umardani (STKIP Singkawang, 2020)
This study aimed to evaluate the 2013 food plant seed breeding training program that adopts Kirk Patrick's approach by using four levels of evaluation stages, namely Reaction Evaluating, Learning Evaluating, Behavior Evaluating, and Results Evaluating. This study was qualitative descriptive. The research informant was the Head of the Food and Horticultural Plant Seed Development Unit of West Kalimantan Province. The training participants were represented by 7 Heads of Seed Garden Installation, one committee, one instructor as a training facilitator, as well as one farmer breeder who did not participate in the training program. Data collection was carried out through observation and in-deft interview techniques with the informants. The results of descriptive analysis showed that the policy context concerning the objectives to be achieved and the program was considered clear according to the majority of informants and also running well. At the Reaction Stage, most of the informants admitted that the time given was too limited: however, the participants were satisfied with the atmosphere of the Food Plant Seed breeding training activities, the instructor was considered to be competent and mastered the learning media so that he was able to motivate the participants to be active in learning, the committee had also worked optimally. At the Learning Stage, the learning method was presented interestingly yet the participants were not yet fully skillful. At the Behavior Stage, the majority of informants from the participants' group acknowledged that there had been a change in behavior which was shown by the improvement of skills after participating in the Food Plant Seed breeding training program. Finally, at the Yield Stage, after a few months of participating in the breeding training of these food crop seeds, there had been a change in production even though has not been able to exceed the production yield of the breeding farmers who did not participate in the breeding training program of these food crop seeds.